Oralidades y resistencias en el Caribe colombiano - Hoyos Guzmán, Angélica; Silva Vallejo, Fabio; Díaz Piñeres, Jesús Elías (CIICLA, Universidad de Costa Rica, 2022)
The article reflects on oral productions and their resistance in the Colombian Caribbean.It is motivated by the idea of ​​decentering aesthetic and political relations that have been privileged in terms of literacy and that have made memory processes and verbal arts inherent to the speech forms of populations invisible on the margins of an aesthetic and literary canon, from the place of the Oralaloteca as an experience of a research and archive group. We start from the extended and disseminated ideas for the treatment of orality in dialogue with some of the oral pieces that have been collected over 17 years and that are systematized in the Oraloteca corpus. The results of the study aim to reflect on the multiplicity of the verbal arts of orality, taking into account the “letrado” prestige that has prevailed in the academy and seeking interdisciplinarity to contextualize and understand the dynamics of the Colombian Caribbean region in its oralities, recognizing its aesthetic and political values.